(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Pathological changes in dental hard tissues formed during tooth development represent a significant problem in modern dentistry. Disturbances in amelogenesis and dentinogenesis may result from genetic, molecular, and systemic factors that affect mineralization processes. This narrative review summarizes current data on the genetic mechanisms underlying pathological changes in enamel and dentin, discusses major hereditary dental disorders, and highlights the prospects of molecular genetic diagnostics in clinical dental practice.